Urbanization and the Evangelical Pulpit in Nineteenth-Century Scotland - Enright, William G. (Church history, 1978)
Urbanization was the child of the industrial revolution. Born in the previous century, urban life rapidly matured in the nineteenth. The growth of industrial centers such as Glasgow placed an unbearable strain on the existing parochial system as people who had been reared in rural ways were thrust into urban situations alien to rural interests. One observer described the movement of the population from country to town as “a flood which swept away all the old relations of urban and rural districts.” The result of this social upheaval was twofold: a widespread attitude of religious disinterest and the appearance of social vices on a large scale. To the staid but wary religious community, urbanization appeared to be the basis of irreligion and moral decadence.